Analysis Overall Equipment Effectiveness (OEE) Using Multiple Linear Regression on the Assembly Coil Line at PT. XYZ - Moh Farhan Athoillah; Harry Ramza (Politeknik Piksi Ganesha Indonesia, 2026)
Production efficiency is a critical factor in the increasingly competitive automotive manufacturing industry. This study analyzes the value of Overall Equipment Effectiveness (OEE) of the Assembly Coil Line at PT. XYZ during February 2026. OEE was evaluated using three main components Availability, Performance Efficiency, and Rate of Quality. Data were collected over 20 working days, with a Planned Production Time of 19,200 minutes and Planned Down Time of 2,880 minutes, resulting in 16,320 minutes of Effective Working Time. The Average OEE reached of 94.48%, comprising Availability of 95.31%, Performance Efficiency of 99.70%, and Rate of Quality of 99,42%, all exceeded the 85% world-class benchmark. Reduced Availability was primarily caused by 670 minutes of unplanned downtime, 36 machine failures, and an average MTBF of 432 minutes. The study recommends implementing Total Productive Maintenance (TPM) and Predictive Maintenance to sustain and further improve production performance.